PRACTICALITY OF A HYBRID BOOK AS READING MEDIA IN AN INCLUSIVE CLASS - Putu Eva Julia Maharani; I G A Lokita Purnamika Utami (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2026)
The purpose of this study is to evaluate the practicality of a hybrid book created to support the educational resources of an inclusive English class at SDN 2 Bengkala. The study employed a Research and Development (R&D) design using the ADDIE model. The study considers research questions related to the practicality of the implemented media. Teachers and students were given practical questionnaires to complete to get the data. The results showed that learning media incorporating multimodal components, such as interactive content, sign language videos, and visual aids, are necessary for inclusive students, particularly those who are deaf and mute. 93% of teachers and 90% of students scored the practicality test as extremely practical, indicating very good practicality. As a result, it is possible to use the hybrid book as an approachable and helpful teaching tool in an inclusive English course. By providing a sustainable media innovation that can be further developed and applied to various disciplines and educational levels, this research advances inclusive education.